Effect of zinc-sulphate treated soybean-meal feeding on nutrient utilization and blood metabolic profile in male Murrah buffalo calves - DASS, R S; KUMAR, RIPUSUDAN; BHADANE, K P; TIWARI, R K; MUDGAL, VISHAL; GARG, A K; VARSHNEY, V P (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted on 15 male buffalo calves (18-months-old, 263.0Â±7.8 kg mean body weight), divided into 3 groups of 5 calves in each, to elucidate the effect of feeding zinc-sulphate treated soybean-meal on nutrient utilization, nitrogen balance and blood metabolic profile. All the buffalo calves were fed on wheat straw and concentrate mixture to meet their nutrient requirement. Concentrate mixture was having 25% untreated, 1% and 2% zinc sulphate treated soybean meal in group 1, 2 and 3, respectively. This feeding practice lasted for 60 days. A metabolism trial was conducted to know the digestibility of nutrients and nitrogen balance at the end of feeding trial. Blood was collected to estimate the blood biochemical profile from all the animals after 60 days of experimental feeding. Results revealed no significant difference in the digestibility of proximate principles and fiber fractions and nitrogen balance. Results revealed non-significant difference in serum concentration of total protein, albumin, globulin, urea, calcium and phosphorus, whereas the concentration of serum cholesterol and blood glucose decreased and serum zinc level increased significantly in group 2 and 3 in comparison to control group. The activity of alkaline phosphatase was significantly higher in calves fed concentrate mixture having zinc sulphate treated soybean meal than the control group calves. There was no significant difference in plasma concentration of T3, whereas levels of plasma T4, testosterone and insulin were significantly higher in groups 2 and 3 as compared to group 1. It may be concluded that addition of zinc sulphate treated soybean meal in concentrate mixture of buffalo calves decreased blood glucose and serum cholesterol concentration and increased the levels of serum alkaline phosphatase, zinc, and plasma hormones like insulin, testosterone and thyroxine, though there was no significant effect on weight gain, digestibility of nutrients and nitrogen balance. Â